FAKTOR-FAKTOR YANG MENJADI PERTIMBANGAN TAMU DALAM MENGINAP DI HOTEL BHINNEKA SURABAYA - Ramansyah Hidayat, Ramansyah Hidayat (Fakultas Ekonomi Universitas 45 Surabaya, 2019)
Hotel competition in the city of Surabaya shows that the hospitality industry in Surabaya continues to increase. This condition makes the company must understand the wishes and needs of guests, by improving the quality of the factors contained in a hotel so that it can attract guests to stay in a hotel. This research was conducted using factor analysis and aims to find out what factors influence the interest of guests to stay at the Bhinneka Surabaya hotel. In addition, the magnitude of the influence of a factor by looking at the value of factor loadings can also be known. The objectives expected from this study are sources of information that management can use if there are similar studies. The results of the study showed that of the 18 original variables, 5 factors were formed which influenced guests in staying at the Bhinneka Surabaya hotel. Factor 1 consists of pramugraha hospitality variables with an influence level of 88.5%, guest equipment with an influence level of 79.8%, and room equipment with a level of influence of 77.8%. Factor 2 affects the consideration of the second largest guest. Factor 2 consists of hotel location variables close to the workplace with an influence level of 76.7%, hotel security with an influence level of 74.6%, extensive hotel parking yard with influence level of 69.1%, hotel location near shopping center with an influence level of 65.7%, and the location of the hotel is easily accessible with an influence level of 63.6%. Factor 3 affects the consideration of the third largest guest. Factor 3 consists of room rate suitability variables with an influence level of 88.6%, receptionist hospitality with an influence level of 87.0%, cleanliness of rooms with an influence level of 72.0%, ease of access in and out of hotels with an influence level of 50, 5%, and the registration process is fast with an influence level of 82.9%. Factor 4 affects the consideration of the fourth largest guest. Factor 4 consists of a variable registration process with a level of influence of 82.9%, the appearance of Pramugraha with a degree of influence of 73.6%, appearance of the receptionist with a level of influence of 73.0%, and handling of complaint rooms with an influence level of 64.9 %. Factor 5 affects the consideration of the fifth largest guest. Factor 5 consists of interior room variables with an influence level of 72.3%, and room types with an influence level of 68.9%.